2020
DOI: 10.1186/s12876-020-1179-6
|View full text |Cite
|
Sign up to set email alerts
|

Elobixibat alleviates chronic constipation in hemodialysis patients: a questionnaire-based study

Abstract: Background: Hemodialysis patients are prone to constipation, which can adversely affect their quality of life (QOL). Elobixibat, a highly selective inhibitor of the ileal bile acid transporter, can increase the bile acid level in the colon and, subsequently, enhance colonic motility and secretion. In hemodialysis patients with chronic constipation, it may have a novel action mechanism. However, the effect of elobixibat on such patients' QOL had not been reported. This study aimed to evaluate the effect of elob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Such studies could also determine whether the treatment of constipation significantly improves HRQoL in this population. In a multicenter, observational study of hemodialysis patients with FC, elobixibat significantly increased the frequency of BM and improved patients' HRQoL 55 . Furthermore, based on mechanistic insights into the “gut-kidney-heart” axis, Sumida and Kovesdy have recently hypothesized that the administration of laxatives might be a gut microbiota-targeted therapeutic intervention for reduction cardiovascular risk in patients with CKD 37 .…”
Section: Discussionmentioning
confidence: 95%
“…Such studies could also determine whether the treatment of constipation significantly improves HRQoL in this population. In a multicenter, observational study of hemodialysis patients with FC, elobixibat significantly increased the frequency of BM and improved patients' HRQoL 55 . Furthermore, based on mechanistic insights into the “gut-kidney-heart” axis, Sumida and Kovesdy have recently hypothesized that the administration of laxatives might be a gut microbiota-targeted therapeutic intervention for reduction cardiovascular risk in patients with CKD 37 .…”
Section: Discussionmentioning
confidence: 95%
“…A recent phase III clinical study showed that elobixibat increased the frequency of spontaneous bowel movements in non-renal impaired patients with chronic constipation ( 9 ). An observational study reported that elobixibat increased the number of spontaneous bowel movements in patients with chronic constipation undergoing hemodialysis ( 13 ). In the present study, elobixibat increased stool frequency in patients with moderate to end-stage CKD, and its effect on improving constipation was similar between patients with CKD stages G3–G5 and G5D.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of SBMs after elobixibat administration was approximately 4.2 times per week, which indicates a normal bowel movement. Kamei et al [39] reported that elobixibat is suitable for patients undergoing dialysis thrice a week to be adjusted to promote defecation within days other than dialysis days; they added that a moderate increase in SBMs may be beneficial. Considering the SCS results after administration, the SCS in the E10 group was significantly lower than that in the L24 and L48 groups.…”
Section: Discussion/conclusionmentioning
confidence: 99%